Investigations of the heterogeneity of host-associated bacteria during respiratory infections - Lamarche, Daphnée (My University, 2020)
Respiratory infections are a leading cause of mortality and morbidity worldwide and will continue to be prevalent in the coming decades. The burden associated with acute respiratory infection is mostly due to the high prevalence of pneumonia, including hospital-acquired pneumonia. Respiratory infections are diverse with respect to clinical features, population targeted, etiology, treatment options, and development of potential complications. Several factors such as the difficulty to identify the etiology of acute respiratory infections and subsequent inappropriate therapeutic plans contribute to the complexity of treating respiratory infections, and to the development of potential complications such as pleural empyema, bacteremia and sepsis. As such, further study of the microbes entering the respiratory tract as potential pathogens or contributing to disease outcome is required. In this thesis, I have investigated the microbiome of the critically ill as part of the PROSPECT study (NCT02462590) which examines probiotics as a prophylactic treatment to reduce ventilator-associated pneumonia in the intensive care unit (ICU). Using 16S rRNA gene profiling, we identified a novel association between hospital mortality and low microbial α-diversity observed in the lower respiratory tract. Interestingly, this microbial signature was readily identifiable within days of patient admission to the ICU. I also carried out quality control on the probiotic (Lactobacillus rhamnosus GG) and investigated the microbiology of adverse events with possible involvement of the probiotic. We demonstrated that the patients enrolled in the PROSPECT study received a constant dose of the probiotic and that 70 % of the placebo used in this study contains no bacteria where the remaining capsules recovered a modest number of non-pathogenic bacteria. Moreover, our results showed that rare adverse events associated with the probiotic consumption could occur, though several events were potentially due to bedside contamination not infection. Additionally, I performed a comparative genomic study of 151 isolates of the Streptococcus Anginosus/Milleri group which represents under-reported respiratory pathogens that may commonly be associated with pneumonia complications such as pleural empyema. This investigation has shown that these isolates are genetically heterogenous, where diversity was observed by the presence and identity of specialized genes and genomic features (e.g. prophages, antimicrobial resistance genes, and biosynthetic gene clusters). Moreover, we further characterized two phenotypically distinct isolates recovered from a single pleural empyema aspirate. The difference in morphotype was the consequence of the presence of a single mutation in a gene involved in exopolysaccharide production. Taken together, this work characterized the heterogeneity associated with respiratory infections. This heterogeneity, from the microbial community, bacterial group, and isolate level, contributes to the challenge of identifying but also treating respiratory infections such as pneumonia and pleural empyema.